Ladies in the laboratory II : West European women in science, 1800-1900 : a survey of their contributions to research - Creese, Mary R. S., 1935- (Scarecrow Press, 2004)
A fascinating analysis of the work of notable women by national group, giving thorough data comparing the contributions of women in choice fields. Among the women presented are more than a few colorful personalities representative of the entire social scale, from a royal princess to the daughter of a Paris slum shopkeeper. Researchers in the field of women's history and science history will find this indexed volume a valuable resource.